2017
DOI: 10.1016/j.foodhyd.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Pectin isolation and characterization from six okra genotypes

Abstract: 20Pectin was isolated by aqueous extraction at pH 6.0 from the pods of six different okra 21 genotypes (Abelmoschus esculentus L.). Genetic diversity was determined using fragment length

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
92
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 165 publications
(109 citation statements)
references
References 48 publications
(61 reference statements)
15
92
2
Order By: Relevance
“…This is a significant development, as it indicates that pectin with diverse structural characteristics could be obtained from different waste streams with little effort. The HG = GalA – Rha molar ratio ranged from 47 to 59% while the RG‐I was between 12 and 20%, which means that all studied pectins are smooth as HG regions are predominant . Furthermore, the RG‐I backbone is typically composed of alternating units of rhamnose and galacturonic acid and therefore the molar ratio of Rha/GalA is virtually 1:1.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This is a significant development, as it indicates that pectin with diverse structural characteristics could be obtained from different waste streams with little effort. The HG = GalA – Rha molar ratio ranged from 47 to 59% while the RG‐I was between 12 and 20%, which means that all studied pectins are smooth as HG regions are predominant . Furthermore, the RG‐I backbone is typically composed of alternating units of rhamnose and galacturonic acid and therefore the molar ratio of Rha/GalA is virtually 1:1.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, the RG‐I backbone is typically composed of alternating units of rhamnose and galacturonic acid and therefore the molar ratio of Rha/GalA is virtually 1:1. The linearity of the isolated fractions may indicate that gelling agents can be obtained from any fraction of lemon pectin although linearity is not always the most important factor …”
Section: Resultsmentioning
confidence: 99%
“…However, rhamnopyranosyl residue was further confirmed in the okra mucilage extract by the signal at 1.24 ppm (Figure b). This is because signals ranging from 1.23 to 1.27 ppm are indicative of the presence of methyl (–CH 3 ) substituent of unbranched α‐(1‐2)‐linked and branched α‐(1‐2) and α‐(1‐4)‐linked rhamnose units (Kpodo et al, ). These data are consistent with data reported by Woolfe et al (), which reported rhamnose residues in okra mucilage.…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H NMR fingerprints of amadumbe and okra dry mucilage extracts showed a broad peak at around 3.75 to 3.84 ppm (Figure 2 a,b), which suggests the presence of methyl groups connecting to carboxyl groups of D -galacturonic acid (Kpodo et al, 2017 ). The doublet at 5.1 and 5.3 ppm (Figure 2 a,b), having a coupling constant of J = 3.9 Hz, may correspond to the anomeric F I G U R E 1 Infrared spectroscopy fingerprints of (a) amadumbe (b) okra mucilage extracts protons of the α-type rhamnopyranosyl and glucopyranosyl residues, respectively (De Bruyn & Anteunis, 1976 ;Fukushi, Onodera, Yamamori, Shiomi, & Kawabata, 2000 ).…”
Section: H Nmr Fingerprints Of Mucilagementioning
confidence: 99%
See 1 more Smart Citation